Some reproductive and productive traits of Sudan Nubian goats - El-Naim, Y.A. (1979)
A flock of 57 Nubian goats had been studied for some reproductive and productive traits at Khartoum University Top Farm. The flock was observed to kid all the year round. Gestation length averaged 146.0±1.1 days. Type of birth, dam age, dam weight and sex had no influence on gestation length interval was observed to be as long as 228±17 day, on average. Litter size was 1.4 kids. Doe age and weight influenced litter size between seasons. Featal kid mortality rate was 12%, rose to 32% during the neonatal life. Overall kid mortality rate was 50%. Type of birth, sex, birth weight, doe age and season influenced kid mortality. Overall birth weight was 2.2±0.19kg. Type of birth, sex, doe age, doe weight and season of kidding had significant effect on kid’s birth weight. The overall body gain was 1.6 kg/month. Male kids grew at a faster rate than female ones. Type of birth had an effect on growth rate. Kid body gain decreased with age. Birth weight was positively correlated with subsequent weights during the preweaning life. Weaning weight was positively correlated with body weights at the 3 and 6 month of age. Average weekly milk yield was 3.5 kg equivalent to 73.5 kg per lactation. Average lactation period was 147 days. Milk production was found to be influenced by doe weight and lactation length and to lesser extent by doe age and number of kids born. Season had no significant effect on milk production. Total milk yield was highly correlated with first month yield, r=0.74.